Bilateral Total Cataract in a Young Patient After Septic Shock: Diagnostic and Therapeutic Approach - Macedo, João Victor Tenório Lossio de; Ávila, Carolina Oliveira de; Carvalho, Pedro Carrión; Kwitko, Lucas Cavinato; Silva, Mariana Vieira Cavalcante da; Rezende, Sarah Correa Soler Albino Titz de; Gomes, Enzo Gallardo; Moreira, Pedro Henrique Santana; Negrine, Isabela Ussifati; Macedo, Júlia Tenório Lossio de; Oliuza dos Santos, Ariane (Brazilian Journal of Case Reports, 2025)
Cataract secondary to severe systemic conditions is a rare but clinically relevant entity, particularly in young patients exposed to intense inflammatory insults such as septic shock. Early identification and timely surgical management can directly impact visual and functional prognosis. To report a case of rapidly progressing bilateral total cataract in a young patient following septic shock, emphasizing clinical presentation, surgical approach, and visual outcomes. This is a qualitative and descriptive case report based on retrospective analysis of medical records, surgical documentation, and ophthalmologic examinations. The patient underwent phacoemulsification with implantation of a monofocal toric intraocular lens in the left eye. Surgery in the right eye is still pending due to financial constraints. The patient demonstrated satisfactory visual recovery in the left eye, with final visual acuity of 20/30. The right eye remains with mature cataract and severely reduced visual acuity. Postoperative follow-up showed good anatomical recovery without complications. This case reinforces the importance of ophthalmologic screening in critically ill patients and highlights that cataract may represent a significant, yet treatable, visual complication following septic shock. Early intervention and the use of advanced intraoperative technologies contribute to favorable visual rehabilitation. Socioeconomic barriers, however, may delay complete visual recovery in vulnerable populations.